Sevoflurane inhibits cell proliferation and migration of glioma by targeting the miR-27b/VEGF axis - Zhan, Xi (Mol Med Rep, 2021)
Poor prognosis in patients with glioma is primarily due to rapid tumor growth and cell invasion and migration. In addition, microRNA (miR)-27b is decreased in metastatic glioma. The present study investigated whether sevoflurane inhibited glioma cell progression by targeting miR-27b. Cell proliferation was analyzed using a Cell Counting Kit-8 assay and a wound healing assay was used to detect cell migration. Western blotting and reverse transcription-quantitative PCR analysis were performed to determine the protein and mRNA expression levels. A dual luciferase assay was used to determine the relationship between vascular epithelial growth factor (VEGF) and miR-27b. VEGF was identified to be a direct target of miR-27b. Moreover, sevoflurane treatment increased the expression of miR-27b and decreased the expression of VEGF in U251 and U87 cells. Compared with the control group, sevoflurane inhibited the proliferation and migration of U251 and U87 cells, as well as the expression of matrix metalloproteinase (MMP)-2 and MMP-9, which were subsequently abolished by pre-treatment with an miR-27b inhibitor. The present results indicated the potential use of sevoflurane by anesthesiologists for the surgical resection of glioma, which may improve patient outcomes in the clinical setting.